THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE AND COMPANY CHARACTERISTICS ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURES - Arifatul Aini; Tita Djuitaningsih (Journal of Social Political Sciences, 2023)
This study aims to examine the effect of environmental performance and company characteristics on corporate social responsibility (CSR) disclosure. The characteristics of the companies in this study are proxied by company size, profitability, leverage, and public ownership. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2019 period, totaling 182 companies. The sampling technique used is the purposive sampling method. Based on this method, a sample size of 148 was obtained. The data analysis method used was the multiple linear regression method. The results show that environmental performance and leverage have a positive effect on CSR disclosure. While profitability has a negative effect on CSR disclosure. Meanwhile, company size and public share ownership have no effect on CSR disclosure.